COVID-19 in Long-Term Care Facilities: A Rapid Review of Infection Correlates and Impacts on Mental Health and Behaviors. (July 2022) - Yang, Haoyue; Rigsby, Matilin; Zhu, Xuemei; Lee, Chanam; Ory, Marcia
Background: Long-term care facilities (LTCFs) with compact, group-living arrangements have become COVID-19 hot spots during the pandemic. Systematic research is needed to understand factors associated with COVID-19 infections in LTCFs and the inadvertent effects of preventive measures adopted by LTCFs. Objectives: This rapid review identifies factors associated with LTCF residents' COVID-19 infections and the impacts of the pandemic and the corresponding preventive measures on residents' mental health and behavioral problems. Methods: Following the preferred reporting items for systematic reviews and meta-analyses guidelines, we identified and reviewed relevant literature in Medline, PsycINFO, and AgeLine. Results: Thirty-seven articles were identified and reviewed, including 30 reporting factors associated with COVID-19 infections in LTCFs and seven reporting the impact of the pandemic and corresponding prevention measures on LTCF residents. Results revealed four domains of factors associated with COVID-19 infections: facility physical environments, resident characteristics, facility management and testing, and community factors. The pandemic and infection control measures increased residents' depression, anxiety, loneliness, and behavioral problems (e.g., agitation, hallucinations). Residents without cognitive impairments were more vulnerable to these adverse effects. Conclusion and implications: LTCF managers/policymakers and healthcare designers can help mitigate COVID-19 infections by (1) providing additional resources to vulnerable LTCFs; (2) enhancing the training of personal protective equipment use and guideline compliance; and (3) investing in amenities, such as sinks, quarantine rooms, and outdoor spaces. Digital activities and accessible green spaces can mitigate mental health and behavior issues. Future LTCF design can benefit from flexible spaces, natural ventilation, and reducing crowding.